Analysis methods of providing information documented in social and communication system - Форкун, Юрій Вікторович (Eastern-European Journal of Enterprise Technologies, 2013)
An import ant part of the development of a set of documents is to create high-quality, meaning full documented in formation of public communication systems documentation that satisfies the needs of both users and experts to support the requirements and development of such systems. Existing approaches to the creation of documented in formation of public communication systems do not involve users and the systems them selves do not use the opportunities for finding, collecting, collating and generation of fragments documented in formation of public communication systems in a hypertext environment, WWW, especially in virtual communities on line. To solve this problem, first make a systematic analysis of DIS and SCS to identify opportunities and potential SCS DIS, which should be considered in two main aspects: - Analysis of socio-community communication as a mechanism and means of forming SIC; - Analysis of SIC created social communication community.